1990
DOI: 10.1002/jts.2490030107
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sexual assault on physical health status

Abstract: This study was conducted to investigate the long‐term physical health implications of sexual assault in the rape victim. Fifty‐one sexual assault victims, each with 2 or more years of time elapsed since the rape, responded to a self‐administered questionnaire composed of demographics items and the Cornell Medical Index‐Health Questionnaire (CMI). The victims were matched by age with a control group of 51 nonvictims. The results showed nonsignificant t‐test differences between the two groups in demographic fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…[34][35][36] In addition, women who report histories of either adult or childhood sexual assault/molestation or rape report higher rates of chronic illnesses, most commonly gastrointestinal and gynecological, but also including respiratory disorders (e.g., asthma, emphysema, and bronchitis), peptic ulcer disease, heart problems, hypertension, arthritis, and diabetes. 34,[36][37][38] Gynecological complaints associated with sexual trauma include dysmenorrhea, excessive menstrual bleeding, sexual dysfunction, 39 abnormal Pap smears, pain in the lower abdomen other than during menstruation, 7 burning sensation in sexual organs, and pain during intercourse. 37 Golding et al 40 interviewed women seeking treatment for severe premenstrual syndrome (PMS) and found that at least one attempted or completed sexual abuse event was reported by 95% of the sample and that 81% of these women reported being raped.…”
Section: Sexual Trauma and Healthmentioning
confidence: 97%
“…[34][35][36] In addition, women who report histories of either adult or childhood sexual assault/molestation or rape report higher rates of chronic illnesses, most commonly gastrointestinal and gynecological, but also including respiratory disorders (e.g., asthma, emphysema, and bronchitis), peptic ulcer disease, heart problems, hypertension, arthritis, and diabetes. 34,[36][37][38] Gynecological complaints associated with sexual trauma include dysmenorrhea, excessive menstrual bleeding, sexual dysfunction, 39 abnormal Pap smears, pain in the lower abdomen other than during menstruation, 7 burning sensation in sexual organs, and pain during intercourse. 37 Golding et al 40 interviewed women seeking treatment for severe premenstrual syndrome (PMS) and found that at least one attempted or completed sexual abuse event was reported by 95% of the sample and that 81% of these women reported being raped.…”
Section: Sexual Trauma and Healthmentioning
confidence: 97%
“…Among teen girls who have had sexual intercourse, this number rises to almost one in five [5]. In addition to injury, victims of dating violence also face higher risk of substance abuse, unhealthy weight control, poorer health, sexual risk behavior, pregnancy, and suicidal behavior [6,7]. Thus, the need for prevention and early intervention programs is clear.…”
mentioning
confidence: 96%
“…4,5,[7][8][9] Most women will not receive psychiatric evaluation or treatment, although the vast majority will receive health care during the period in which they have symptomatic PTSD. Women who are victims of rape or sexual assault are twice as likely to seek medical services than nonvictims 10,11 and often seek medical services much more often than psychological services in the year after being assaulted (72.6% compared with 19%). 12 Thus, because of the high prevalence rates of trauma and PTSD in women, accurate screening and prompt diagnosis of women presenting for gynecologic primary care is important, so that treatment can be initiated.…”
mentioning
confidence: 98%